The Effectiveness and Contradictions of the Kampung Keluarga Berkualitas (Quality Family Village) Program: A Critical Analysis of Community Participation and Gender Justice in Yogyakarta, Indonesia - Itriyati, Fina; Rohmah, Annisa Nur (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2026)
This article examines the shift in Indonesia’s family planning program from a centralized model to the participatory Kampung Keluarga Berkualitas (Quality Family Village), formerly Kampung KB, approach. Despite this shift, a substantial gap persists between policy objectives and grassroots realities, particularly in relation to patriarchal structures that constrain women’s autonomy and the limited implementation of interventions that promote genuine empowerment. Based on a qualitative case study of Kampung KB Bugel in Yogyakarta, this study employed a hybrid data collection strategy adapted to the conditions of the COVID-19 pandemic. Data were collected through a combination of on-site observations, virtual interviews, and focus group discussions, along with a review of official BKKBN (National Population and Family Planning Board) documents. The findings indicate that local working groups, Pokja (working groups), and community service initiatives established institutional frameworks and generated small-scale economic benefits through UPPKS (Family Income Improvement Program) microenterprises. Although this participatory model generated meaningful community interest, it continued to face significant obstacles. A central concern was that women’s involvement in working groups and economic programs unintentionally increased their double burden. In addition, limited budgets, overlapping programs, and insufficient understanding among village government actors constrained program implementation. Ultimately, this article argues that unless deeply rooted patriarchal norms are addressed, Kampung KB risks creating an illusion of empowerment rather than advancing substantive gender equity. To prevent this outcome, policies designed at higher administrative levels must be better synchronized with the everyday realities of grassroots communities.